Pancasila sebagai dasar pendidikan anti korupsi untuk generasi muda indonesia - Prayoda, Muhammad Wendry (Maliki Interdisciplinary Journal, 2025)
Corruption remains a serious problem that hinders national development and damages the character of the nation. Efforts to eradicate corruption cannot rely solely on law enforcement, but must also be supported by moral education and character building from an early age. This study aims to examine the role of Pancasila values as a foundation in the development of anti-corruption education for Indonesia's younger generation. Using a qualitative descriptive method through a literature study approach, this research explores various sources such as scientific journals, anti-corruption institution reports, and other academic references. The findings of the study state that Pancasila values, such as honesty, responsibility, justice, and a spirit of togetherness, are closely related to shaping an anti-corruption character. Integrating these values into the education curriculum, instilling honest behaviour, and involving the active role of families and communities can strengthen the integrity of the younger generation. Therefore, anti-corruption education based on Pancasila is an effective strategic step to produce a future generation with integrity, high morals, and a commitment to creating a corruption-free Indonesia.